Incidence of Colorectal Cancer in Saiful Anwar Hospital, Malang January 2010- April 2015 - Lia Sasmithae; Syifa Mustika (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy, 2017)
Background: Colorectal carcinoma is the third most common malignancy worldwide and the second most frequently found cause of mortality in the United States. In Indonesia, the number of colorectal cancer patients ranks 10th (2.75%) after other cancers (cervical, breast, lymph nodes, skin, nasopharyngeal, ovarium, soft tissue, and thyroid). The main key to success in managing this carcinoma is by detecting the cancer in early stage to enable curative treatment to be performed. But, unfortunately most patients in Indonesia seek for treatment in the advanced stage, causing low survival rate. Colorectal carcinoma requires multimodalities management and there is no uniformity of management approach in the national level. This study was aimed to identify the incidence, epidemiology, and risk factors which influence the occurrence of colon and rectal cancer in Saiful Anwar Hospital (SAH), Malang based on colonoscopy examination from January 2010-April 2015.